Power Led' Outside Intervention in Kurdish Politics in Iraq and Turkey in the Early 1970s - SEVER, AYŞEGÜL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
The article addresses the issues involved in Turkey's watchful neutrality vis-a-vis the Kurdish mobilization and the temporary autonomy deal in Iraq during the 1970s. Regardless of Ankara's long-held concerns about the spillover effects of the cross-border ethnic issues and growing outside assistance to the Kurdish insurgency by the US, Iran and Israel against Baghdad, Turkey stood aloof to the internationalisation of the Kurdish developments in Iraq. The successive governments in Turkey generally saw the Kurdish-Baghdad confrontation throughout the 1960s and early 1970s in the context of the Cold war and therefore were able to overlook its possible implications on its own Kurds, especially in view of the assurances extended to itself by its allies involved. Having no acute perception of vulnerability due to international conjuncture, the relations with the allies and domestic politics, Turkey seemed not to have any particular instrumental, affective or humanitarian motives to actively get involved in the then significant Kurdish developments in Iraq.
Keywords: ETHNIC-CONFLICT